Differential Excretory/Secretory Proteome of the Adult Female and Male Stages of the Human Blood Fluke, Schistosoma mansoni - Kenney, Eric T.; Mann, Victoria H.; Ittiprasert, Wannaporn; Rosa, Bruce A.; Mitreva, Makedonka; Bracken, Bethany K.; Loukas, Alex; Brindley, Paul J.; Sotillo, Javier (Frontiers in Parasitology, 2022)
Intricate molecular communication between schistosome flatworms and their mammalian host, as well as between paired male and female schistosomes has shaped the secreted proteome of these flatworms. Whereas the schistosome egg is responsible for the disease manifestations of chronic schistosomiasis, the long lived, adult female and male stages also release different mediators including glycans, lipids, proteins and small molecules, known as excretory/secretory products (ESPs), that facilitate their survival. Given their importance, deeper analysis focused on analyzing the ESPs from adult schistosomes would likely be informative, beyond current understanding of the complement of ESP proteins. Here, taking advantage of highly accurate and sensitive mass spectrometers, the excretory/secretory proteome from cultured Schistosoma mansoni male or female adult worms was identified, quantified, compared and contrasted using a label-free proteomic approach. Approximately 1,000 proteins were identified, from which almost 800 could be quantified. Considering the proteins uniquely identified and proteins with a significantly regulated expression pattern in male or female flukes, a total of 370 and 140 proteins were uniquely or more abundantly secreted by males and females, respectively. Using functional analysis networks showing the gene ontology terms and KEGG pathways with the highest significance, we observed that male schistosomes secrete proteins related to carbohydrate metabolism and cytoskeletal organisation more abundantly than females, while female worms secreted more hydrolases and proteins involved in cellular homeostasis than males. This analysis doubles the number of reported excreted/secreted proteins from S. mansoni, contributing to deeper understanding of the host-parasite interaction and parasitism. Furthermore, these findings expand potential vaccine and diagnostic candidates for this neglected tropical disease pathogen, and thereby also provide leads for novel intervention to control this disease and its transmission.